Are Chinese pediatricians missing the opportunity to help parents quit smoking?. Issue 1 (December 2016) - Liao, Jing; Winickoff, Jonathan; Nong, Guangmin; Huang, Kaiyong; Yang, Li; Zhang, Zhiyong; Abdullah, Abu
Abstract Background Secondhand smoke (SHS) exposure of children due to parental tobacco use is a particularly prevalent health issue and is associated with adverse health outcomes. Following the US Clinical Practice guidelines, pediatricians in the United States deliver 5A's (ask, advise, assess, assist, and arrange) counseling to smoking parents which has proven to be effective. We examined Chinese pediatricians' adherence to the clinical practice guidelines for smoking cessation (i.e. 5A's counseling practices) with smoking parents, and identified factors associated with these practices. Methods A cross-sectional paper-and-pencil survey of pediatricians was conducted in twelve conveniently selected southern Chinese hospitals. Factors associated with any of the 5A's smoking cessation counseling practices were identified by logistic regression. Results Of respondents (504/550), only 26 % routinely provided 5A's smoking cessation counseling to smoking parents. More than 80 % of pediatricians didn't receive formal training in smoking cessation and had not read China smoking cessation guidelines; 24 % reported being "very confident" in discussing smoking or SHS reduction with parents. Pediatricians who had never smoked (OR: 2.29, CI:1.02-5.12), received training in smoking cessation (OR: 2.50, CI:1.40-4.48), had read China smoking cessation guidelines (OR: 2.17, CI:1.10-4.26), and felt very (OR: 7.12, CI:2.45-20.70) or somewhat (OR: 3.05, CI:1.11-8.37) confident in delivering cessation counseling were more likely to practice 5A's. Pediatricians who reported "it is hard to find a time to talk with parents" (OR: 0.32, CI: 0.11-0.92) or "lack of a standard of care requiring pediatricians to provide smoking cessation or SHS exposure reduction intervention" (OR: 0.45, CI: 0.21-0.98) as a barrier were less likely to follow the 5A's guidelines. Conclusions Smoking cessation counseling to address parental smoking is infrequent among Chinese pediatricians. There is a need to develop and test intervention strategies to improve the delivery of 5A's smoking cessation counseling to parental smokers.